PEMUTUSAN HUBUNGAN KERJA SECARA SEPIHAK (Studi Kasus Putusan Mahkamah Agung Nomor. 26 K/Pdt.Sus-PHI/2019) (Lex Jurnalica, 2020)
Termination of Employment is the most common cause in Industrial Relations Disputes. Regarding Industrial Relations Disputes regulated in Act Number 2 of 2004 concerning Industrial Relations Disputes Settlement. With the enactment of Law No. 2 of 2004, provides a clear position regarding disputes arising in Industrial Relations. Settlement of disputes arising in Industrial Relations according to Law No. 2 of 2004 can be done in 2 (two) ways, namely through out-of-court channels (Mediation, Conciliation, Arbitration) and through the Industrial Relations Court at the District Court where the agreement is held. That the employment relationship between the Cassation Applicants / Plaintiffs and the Cassation Respondent / Defendants is bound based on the Sea Work Agreement (PKL) as regulated in article 395 KUHD article 1 number 5 and article 18 Government Regulation Number 7 Year 2000 Concerning Maritime, Article 1 number 5 Permenhub Number 84 of 2003 concerning Recruitment and Placement of Juncto Ship Crews Act Number 17 of 2008 concerning Shipping. The Sea Work Agreement is special (Lex Specialis), so the